KOMPLEKSITAS HUBUNGAN KEPENDUDUKAN DAN LINGKUNGAN - Ella Lesmanawaty Wargadinata (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2021)
The interaction between population and the environment has always been the center of attention when the population is rise high, while the world has not increased by an inch. The factor of population growth blaming as the source of the problem when the environment is degraded. The relationship between the two is often seen as a simple and linear relationship, but when looking deeply, it shows differently. Relationships become increasingly non-linear and complex when it comes to concepts related to population dynamics, such as the number, the growth rate, the population composition, or the density and migration, analysis of relations requires an explanation of variables other than population. The paper is compiled based on a literature review by elaborating on contrast concepts to obtain a comprehensive analysis of the complex relationship between population and environment. This paper discusses the development of population theories and concepts, ranging from pessimistic groups from Malthusian to Neo-Malthusian, and from optimistic groups such as the Boserupian and Cornucopian concepts. The paper then discusses the relationship between population and environment by identifying the presence of mediating factors which come as intermediate factors. Several studies mention that mediating factors include technology, institutional, policy, social, economic, and cultural factors. Environmental damage does not only occur due to population pressure but when mediating factors fail as the buffer to preserve the environment.